FRI0547 Predictive Factors of TMJ Involvement in 230 Consecutive JIA Patients Regularly Screened from 2000 to 2014 in A Single Pediatric Rheumatology Centre. (10th June 2014) - Gattinara, M.; Del Giudice, E.; Lodi-Rizzini, S.; Pontikaki, I.; Romano, M.; Meroni, P.L.; Gerloni, V.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) has been shown to involve frequently the temporo-mandibular joint (TMJ). An important prognostic aspect is to diagnose and treat it promptly. Objectives: To evaluate in a consecutive JIA patients (pts) cohort, regularly screened from year 2000 to 2014, the predictive factors of the TMJ involvement. Methods: 230 consecutive pts (152 females, 78 males) affected by JIA according to ILAR classification, 164 oligoarthritis, 4 polyarthritis rheumatoid factor (RF) +, 34 polyarthritis RF-, 22 systemic onset JIA (soJIA), 4 enthesitis-related arthritis (ERA) HLA B27+, and 2 psoriatic arthritis were included in a retrospective evaluation. Mean disease onset age was 6.5 yrs (range 1-16), mean disease duration 12.7 yrs (range 0.2-46.2). We analyzed the correlation between TMJ involvement with the following items: ILAR categories, age at onset, gender, pattern of articular involvement (large joints, small ones, hips, cervical spine). Results: 88/230 patients (38.3%), 36.8% of females and 41% of males showed a clinical TMJ involvement. Mean age at onset (or diagnosis) of TMJ involvement was 8.3 yrs. 62/88 pts (70.5%) had a bilateral clinical signs of condylar alteration. The involvement of TMJ was observed in 38.3% of the whole population (54.5% of oligoarthritis, 27.3% polyarthritis RF negative, 2.3% polyarthritis RF positive, 9.1% soJIA, 4.5% ERA and 2.3% juvenile psoriatic arthritis) 3 cases (2 females and 1 male) presented with an involvement of TMJ at the diagnosis of JIA. The rate of TMJ involvement was higher in the pts with an early onset of the disease (52.3% in the 0-6 yrs group, vs 36.4% in 7-12 yrs group and 11.3% in 13-16 yrs group). In 56/88 pts (63.3%) TMJ disease was associated with an involvement of large joints, in 4/88 (4.54%) with small joints, in 24/88 (27.7%) with hips and in 18/88 (20.45%) with cervical spine. Conclusions: An early onset of JIA, the oligoarticular ILAR category and a pattern of large joints involvement seem correlated with a higher rate of TMJ disease. Predictive factors of TMJ involvement should be confirmed in a larger JIA population and may be useful for clinicians to adopt appropriate prevention strategies of TMJ disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5816